2013
DOI: 10.1021/ol403166p
|View full text |Cite
|
Sign up to set email alerts
|

Rh(III)-Catalyzed Coupling of Benzamides with Propargyl Alcohols via Hydroarylation–Lactonization

Abstract: Rh(III)-catalyzed C-H activation and annulation of 1-benzoylpyrrolidine with propargyl alcohols has been achieved for an efficient synthesis of (4-benzylidene)isochroman-1-one. Highly enantioenriched products were obtained starting from optically pure propargyl alcohols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(30 citation statements)
references
References 66 publications
0
29
0
Order By: Relevance
“…Established synthetic approaches include Mizoroki-Heck [2] and Fujiwara-Moritani reactions, [3] as well as various catalytic cross-couplings of organometallic reagents with alkynes. [4] C À Hh ydroarylations of alkynes are advantageous over these processes,b ecause they require neither prefunctionalized substrates nor oxidants.S ince the pioneering studies by Murai and co-workers, [5] various metals have been found to efficiently catalyze the hydroarylation of alkynes,for example Ru, [6] Rh, [7] Re, [8] Co, [9] and others. [10] However, these CÀH functionalizations are highly regioselective only when directed by ketone,p yridine,a mide,s ulfoxide,o ro ther strong directing groups,groups which need to be synthesized in additional reaction steps and are not easily removed.…”
mentioning
confidence: 99%
“…Established synthetic approaches include Mizoroki-Heck [2] and Fujiwara-Moritani reactions, [3] as well as various catalytic cross-couplings of organometallic reagents with alkynes. [4] C À Hh ydroarylations of alkynes are advantageous over these processes,b ecause they require neither prefunctionalized substrates nor oxidants.S ince the pioneering studies by Murai and co-workers, [5] various metals have been found to efficiently catalyze the hydroarylation of alkynes,for example Ru, [6] Rh, [7] Re, [8] Co, [9] and others. [10] However, these CÀH functionalizations are highly regioselective only when directed by ketone,p yridine,a mide,s ulfoxide,o ro ther strong directing groups,groups which need to be synthesized in additional reaction steps and are not easily removed.…”
mentioning
confidence: 99%
“…Established synthetic approaches include Mizoroki-Heck [2] and Fujiwara-Moritani reactions, [3] as well as various catalytic cross-couplings of organometallic reagents with alkynes. [4] C À Hh ydroarylations of alkynes are advantageous over these processes,b ecause they require neither prefunctionalized substrates nor oxidants.S ince the pioneering studies by Murai and co-workers, [5] various metals have been found to efficiently catalyze the hydroarylation of alkynes,for example Ru, [6] Rh, [7] Re, [8] Co, [9] and others.[10] However, these CÀH functionalizations are highly regioselective only when directed by ketone,p yridine,a mide,s ulfoxide,o ro ther strong directing groups,groups which need to be synthesized in additional reaction steps and are not easily removed.Arguably,t he most advantageous directing groups in ortho-functionalizations are carboxylates,b ecause benzoic acids are widely available in great structural diversity and at low cost, and can subsequently be derivatized further, utilized as leaving groups in decarboxylative couplings, [11] or removed tracelessly by protodecarboxylation.[12] However,t he weak coordinating ability of this group poses additional challenges in the development of regiospecific CÀH-activating processes. In recent years,s ubstantial advances in carboxylate-directed CÀHa ctivation have been made, [13] for example,b yt he groups of Yu, [14] Miura, [15] Ackermann, [16] and Larrosa, [12b,c] as well as our own group.…”
mentioning
confidence: 99%
“…In 2013, Li and coworkers reported a Rh(III)-catalyzed annulation of 1-benzoylpyrrolidine with propargyl alcohols for the synthesis of (4-benzylidene) isochroman-1-ones (Scheme 6.27) [43]. Highly enantioenriched lactones could be isolated by employing the optically pure propargyl alcohols as the starting materials.…”
Section: Other Six-membered Oxygen-containing Heterocyclesmentioning
confidence: 99%